Perubahan Perubahan Ekologi dan Bencana” Banjir Bandang di Gunung Wilis dan dampaknya bagi Masyarakat Desa Pucangan Tulungagung, 1976. - Latif Kusairi; Andriyanto (Universitas Veteran Bangun Nusantara, 2024)
The increasing population has led to excessive exploitation of natural resources, particularly through forest exploration, which serves as an environmental buffer. As a result, the risk of natural disasters, such as floods, has risen in several regions of East Java, especially in Kediri and Tulungagung. High rainfall and ecosystem changes due to human activities have worsened the situation, causing flash floods that damage infrastructure and residential areas. Both local and central governments have implemented various mitigation efforts, including direct inspections, aid distribution, and transmigration programs. However, long-term solutions require a more comprehensive approach, encompassing environmental conservation and sustainable spatial planning policies. One significant flood event occurred in Pucangan Village, Tulungagung Regency, which resulted in numerous casualties and environmental destruction. Keywords: Flood, Forest Exploration, Disaster Mitigation, Pucangan